A textbook on food contamination and safety - Nambiar, Vanisha (India, 2004)
The book covers all important aspects of food safety and includes additional information on food standards and institutions dealing with problems of food adulteration.
Keywords: Food Contaminants; Food Contamination; Food Safety; Food Standards